Analysis of flexural concrete beams prestressed with basalt composite bars. Analytical-experimental approach. (1st July 2020) - Atutis, Mantas; Kawashima, Shiho
Abstract: This present work describes the complex analysis of flexural concrete members prestressed with basalt fiber reinforced polymer (BFRP) bars considering consecutive phases of the loading applied. The aim of this research was to propose analytical approach for the prediction of effective prestress force that directly influence the serviceability limit state of prestressed concrete members, in particular to deflections. Proposed method considering prestress losses for deflection estimation is based on the concept of prestressed concrete laws within particular assumptions. The method is based on strain and curvature analysis, effective moment of inertia including decompression effect and early aging effects of both the concrete and BFRP. The instantaneous and time-dependent prestress losses, cross-sectional stress-strain, deflection and cracking behavior of concrete members reinforced with BFRP bars are described as an interrelated process. This complex approach allows to avoid disappearing of prestressing effect, such as camber or strain of decompression, as a base point and the principle of serviceability analysis of prestressed concrete members. Also, an experimental program was expanded with the purpose to evaluate the influence of prestress level for flexural stiffness of the real scale concrete beams prestressed with BFRP bars.